2020
DOI: 10.3233/jad-200547
|View full text |Cite
|
Sign up to set email alerts
|

Dementia Care in Times of COVID-19: Experience at Fundació ACE in Barcelona, Spain

Abstract: Background: Fundació ACE is a non-profit organization providing care based on a holistic model to persons with cognitive disorders and their families for 25 years in Barcelona, Spain. Delivering care to this vulnerable population amidst the COVID-19 pandemic has represented a major challenge to our institution. Objective: To share our experience in adapting our model of care to the new situation to ensure continuity of care. Methods: We detai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0
3

Year Published

2020
2020
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 44 publications
(63 citation statements)
references
References 8 publications
(4 reference statements)
1
58
0
3
Order By: Relevance
“…Also, day hospitals, social centres, and other adult day centres were closed as well as possibly home assistance of carers decreased. A report from a non-profit organization providing care to persons with cognitive disorders and their families in Barcelona, reported a significant increase in assistance to guarantee the continuity of care during the lockdown ( Benaque et al, 2020 ). Nevertheless, we found a significant increase in psychiatric emergency assistance during the COVID-19 outbreak of patients with dementia and intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
“…Also, day hospitals, social centres, and other adult day centres were closed as well as possibly home assistance of carers decreased. A report from a non-profit organization providing care to persons with cognitive disorders and their families in Barcelona, reported a significant increase in assistance to guarantee the continuity of care during the lockdown ( Benaque et al, 2020 ). Nevertheless, we found a significant increase in psychiatric emergency assistance during the COVID-19 outbreak of patients with dementia and intellectual disability.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic forced Memory Clinics worldwide to close their face-to-face consultations and non-pharmacological interventions for dementia, such as cognitive therapy, exercise and socialization, have been suddenly stopped during lockdown (Benaque et al, 2020;Brown et al, 2020). Many centers, though, took action and implemented telemedicine in order to continue assisting patients during the pandemic, both for their scheduled follow-up visits but also for urgent consultations (Benaque et al, 2020;Ousset and Vellas, 2020;Padala et al, 2020). This continued care during the pandemic has been especially important for those patients and caregivers in a more vulnerable situation.…”
Section: Covid-19 Indirect Effects In Patients With Dementiamentioning
confidence: 99%
“…The third study reported a total of 84 people with confirmed or suspected COVID-19 among the users of a memory unit and day care centre for people with cognitive disorders in Barcelona (Spain), with a CFR of 44.1%. 49 Evidence on outcomes in long-term care residents compared to others Seven of the included studies compared outcomes in people who contracted COVID-19 between long-term care users and others. These studies generally found that long-term care users had worse outcomes, including higher 28-day-mortality (unadjusted odds ratio for death of nursing home or residential home residents admitted to hospital compared to non-residents: 6.19, 95% CI 3.32-11.8), 23 30-day-mortality (25.3%, 95% CI 24.2-26.4%, among nursing home residents who contracted COVID-19 and were registered in a primary care database compared to 4.0%, 95% CI 3.9-4.2%, among all other people with COVID-19 in the database), 38 and overall mortality (incidence rate ratio for COVID-19 mortality comparing Ontario long-term care residents to community-living adults 70 years and older: 13.1, 95% CI 9.9-17.3), 27 as well as increased risk of complicated disease (odds ratio for deteriorating disease, admission to ICU, or death, comparing nursing home residents to non-residents over 65 years of age: 2.48, 95% CI 1.29-4.65).…”
Section: Evidence On Hospitalisations and Icu Admissions From Institumentioning
confidence: 99%